Regional differences and dynamic evolution of quality medical resources in Chongqing, China. - Liao, Jiale; Jiang, Qianyu; Yu, Haidong; Luo, Yining; Luo, Lin (Humanities & Social Sciences Communications, 2025)
Quality medical resources (QMR) play a crucial role in population health, and their spatial distribution disparities remain a significant cause of health inequities. This study constructs the quality medical resources composite index (QMRCI) using panel data from Chongqing (2015–2023), applying the Dagum Gini coefficient, kernel density estimation, Markov chain, and spatial autocorrelation methods to systematically analyze regional disparities, evolutionary trends, and spatial clustering characteristics of QMRCI, combined with overlay analysis of population density and per capita GDP. The results show that while Chongqing's overall CQMRI allocation has improved, significant interregional disparities persist, exhibiting a gradient pattern of "core polarization - new area emergence - peripheral lag" with notable path dependence and neighborhood effects. In spatial terms, QMRCI demonstrates significant positive clustering and spatial dependence characteristics. Although developed areas concentrate QMRCI, they demonstrate mismatches with population and GDP distributions, whereas less developed areas with fewer QMRCI show better matching degrees. The study recommends enhancing medical resource supply efficiency in densely populated (developed) areas while optimizing regional coordination mechanisms to prevent low-level homogenization. It emphasizes aligning GDP growth with medical resource investment increases, particularly improving resource accessibility in peripheral (less developed) regions. To achieve this, Chongqing should establish a comprehensive dynamic balancing mechanism and targeted policy intervention system to strengthen the healthcare system's overall resilience, ultimately realizing coordinated development of structural optimization and equity improvement.